Development of cobalt-doped alumina hybrids for adsorption of textile effluents - Kousar Parveen; Uzaira Rafique (Adsorption Science & Technology)
The discharge volume and composition of textile effluents gain scientific concern due to hazardous and biotoxic nature of azo dyes. Azo dyes are non-biodegradable due to its complex molecular structure and recalcitrant nature. Serious attempts have been made to synthesize and develop new materials to combat the environmental problems. The present study is designed for removal of azo dyes (Methyl orange, Congo red and Basic fuchsine) from synthetic aqueous solutions and real textile effluents. For this purpose, cobalt-doped alumina hybrids are synthesized and applied as adsorbents in batch experiment. Two different aluminium precursor (aluminium nitrate and spent aluminium foil) and glucose are mixed following sol–gel method to get hybrids. The synthesized hybrids are characterized for surface and bulk properties using Fourier transform infrared, scanning electron microscopy and energy dispersive X-ray techniques. The characterization of materials under Fourier transform infrared revealed that –OH (3487–3504 cm −1 ), C–H (2935–2985 cm −1 ), Al–O–C (∼1380 cm −1 ), Al–O (∼ 800 cm −1 ), Al–O–Al (659–669 cm −1 ) and Co–O (583–589 cm −1 ) groups participate in the binding of dyes onto the surface of hybrids. Amorphous shaped particles and elemental composition (carbon, aluminium and oxygen) are demonstrated in scanning electron microscopy–energy dispersive X-ray micrograph. Time-dependent batch experiments under identical experimental parameters showed 74% of basic fuchsine, 68% of methyl orange and 85% maximum removal of Congo red onto the surface of cobalt-doped alumina hybrids probably through ion exchange mechanism. The experimental data when treated with adsorption models and isotherms, pseudo-second-order kinetic and Freundlich isotherm are found to be best fitted. The present study accomplishes the successful synthesis of novel and efficient cobalt-doped alumina hybrids provides environmental friendly and economical alternative option to the commercial adsorbents for the treatment of textile effluents.